PENGARUH PEMBERIAN MINYAK ZAITUN TERHADAP PENYEMBUHAN ULKUS DIABETES MELITUS PADA PASIEN DIABETES MELITUS TIPE II - Hariati, Hariati; Ginting, Sulastri (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
Diabetes Mellitus is the most common degenerative disease found. This disease is characterized by increased blood sugar levels and high levels of sugar in the urine due to impaired insulin secretion. Diabetes comes from the Greek word (diabainen) which means